Beneficial effects of urine-derived stem cells on fibrosis and apoptosis of myocardial, glomerular and bladder cells. (15th May 2016) - Dong, Xingyou; Zhang, Teng; Liu, Qian; Zhu, Jingzhen; Zhao, Jiang; Li, Jia; Sun, Bishao; Ding, Guolin; Hu, Xiaoyan; Yang, Zhenxing; Zhang, Yuanyuan; Li, Longkun
Abstract: Urine-derived stem cells (USCs) are isolated from voided urine and display high proliferative activity and multiple differentiation potentials. The applicability of USCs in the treatment of bladder dysfunction and in cell-based urological tissue engineering has been demonstrated. Whether they could serve as a potential stem cell source for the treatment of diabetes mellitus (DM) and its complications has not been investigated. Here, we report the repairing and protective effects of USCs on pancreatic islets, the myocardium, the renal glomerulus and the bladder detrusor in diabetic rat models. Type 2 diabetic rat models were induced by means of a high fat diet and intraperitoneal injection with streptozotocin. USCs isolated from voided urine were administered via tail veins. The functional changes of pancreatic islets, left ventricle, glomerulus and bladder micturition were assessed by means of insulin tolerance tests, echocardiography, urine biochemical indexes and cystometry. The histologic changes were evaluated by hematoxylin and eosin staining, Masson's trichrome staining and TUNEL staining. Treatment with USCs significantly alleviated the histological destruction and functional decline. Although the USC treatment did not decrease fasting blood glucose to a significantly different level, the fibrosis and apoptosis of the myocardium, glomerulus and detrusor were significantly inhibited. This study indicates that administration of USCs may be useful for the treatment of the complications of DM. Highlights: This is the first study to investigate the therapeutic effects of USCs on T2D rats. . Injected USCs can differentiate into PDX1-positive cells in rat pancreas. Ameliorating the fibrosis and inhibiting cell apoptosis is the possible pathway for the treatment of complications. USCs are good resource for the treatment of diabetes mellitus and diabetic complications.